Aspects of knowledge, attitude, and practices about COVID-19 in basic education students: A meta-analysis - Ritchelle W. Origenes (JPBI (Jurnal Pendidikan Biologi Indonesia), 2023)
Updated scientific material is needed to incorporate research-based COVID-19 interventions and strategies into basic education. This meta-analysis examined basic education students' COVID-19 Knowledge, Attitude, and Practices (KAP) across the globe. This study identified KAPs needed to integrate COVID-19 into Basic Education after the meta-analysis. Thirteen published studies on basic education students' KAPs toward COVID-19 were analyzed using meta-analysis. PRISMA was utilized in this study. JBI and STROBE checklists assessed these studies' quality. Three low-quality and ten high-quality published studies were identified. Sensitivity and subgroup analyses were used due to the studies' heterogeneity. Low-quality studies had higher KAP pooled levels. Although the pooled KAPs on COVID-19 between the study groups of elementary students only, elementary and high school students, and high school students only were only slightly different, more high school students had good and better KAPs toward COVID-19. Globally, basic education students had high COVID-19 KAPs. There were items in KAPs identified as essential topics for science lesson integration. These six items were identified as essential topics for lesson integration in knowledge, five in attitude, and four items in practice.